2005
DOI: 10.1111/j.0013-8703.2005.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional resources used by the invasive maize pest Diabrotica virgifera virgifera in its new South‐east‐European distribution range

Abstract: Food utilization by adults of the invasive maize ( Zea mays L.) (Poaceae) pest western corn rootworm (WCR; Diabrotica virgifera virgifera LeConte) (Coleoptera: Chrysomelidae) was investigated in the south-eastern part of its new European distribution range. At weekly intervals over a 10-week period, 10 beetles per field were collected from six fields that had a high abundance of flowering weeds and six fields with a low abundance of flowering weeds, with the aim of understanding adult feeding behaviour in Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 24 publications
(32 reference statements)
4
51
0
Order By: Relevance
“…Western corn rootworms have been observed in southeastern Europe dispersing from maize fields to feed on other plants such as sunflower (Helianthus annuus), alfalfa (Medicago sativa), or flowering weeds present in field margins (79). Campbell & Meinke (11) reported that western corn rootworms moved frequently between the maize and prairie interface in east and central Nebraska study sites depending on the phenology of plants that served as food sources.…”
Section: Genetic Bottleneckmentioning
confidence: 99%
See 1 more Smart Citation
“…Western corn rootworms have been observed in southeastern Europe dispersing from maize fields to feed on other plants such as sunflower (Helianthus annuus), alfalfa (Medicago sativa), or flowering weeds present in field margins (79). Campbell & Meinke (11) reported that western corn rootworms moved frequently between the maize and prairie interface in east and central Nebraska study sites depending on the phenology of plants that served as food sources.…”
Section: Genetic Bottleneckmentioning
confidence: 99%
“…Economic losses on a global scale far exceed the $1 billion estimate since the western corn rootworm has continued to spread across Europe (40,44). Larvae of this univoltine chrysomelid feed on roots of maize and some other grass species (8, 9, 15, 91), and adults consume primarily leaf tissue, silks, tender kernels, and pollen (79). The insect overwinters as eggs which are laid in the soil of maize fields from late July through early September and from which larvae hatch the following spring.…”
Section: Introductionmentioning
confidence: 99%
“…It was first detected near Belgrade (Serbia) in 1992, but has since spread across the continent (Hummel, 2003;Kiss et al, 2005a;Boriani et al, 2006;Ciosi et al, 2008;Gray et al, 2009;Meinke et al, 2009), resulting in well-established populations in approximately 19 European countries (EC, 2012). 5 It is expected that this invasive pest species will expand further in the EU (Hemerik et al, 2004;Moeser and Vidal, 2005;Ciosi et al, 2011;Aragón and Lobo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chrysomelid beetles (e.g. Diabrotica virgifera) feed from the maize silks, tender kernels, and pollen (Culy et al, 1992;Moeser and Vidal, 2005). Corn leaf aphids (CLA; Rhopalosiphum maidis), similar to other phloem sapfeeding aphids, use their slender stylets present in their piercing/sucking mouthparts to consume nutrients from the phloem sap that otherwise are used by the plants for their normal growth.…”
mentioning
confidence: 99%